Specificity and action pattern of heparanase Bp, a β-glucuronidase from Burkholderia pseudomallei. (30th May 2019) - Yu, Yanlei; Williams, Asher; Zhang, Xing; Fu, Li; Xia, Ke; Xu, Yongmei; Zhang, Fuming; Liu, Jian; Koffas, Mattheos; Linhardt, Robert J
Abstract: The specificity and action pattern of a β-glucuronidase derived from the pathogenic bacteria Burkholderia pseudomallei and expressed in Escherichia coli as a recombinant protein has been evaluated. While this enzyme shows activity on a number of glycosaminoglycans, our study has focused on its action on heparin, heparan sulfate and their biosynthetic intermediates as well as chemoenzymatically synthesized, structurally defined heparan sulfate oligosaccharides. These heparin/heparan sulfate (HP/HS) substrates examined varied in size and structure, but all contained an uronic acid (UA) residue β-(1→4) linked to a glucosamine residue. On the substrates tested, this enzyme (heparanase Bp) acted only on a glucuronic acid residue β-(1→4) linked to an N -acetylglucosamine, N -sulfoglucosamine or N -acetyl-6- O -sulfoglucosamine residue. A substrate was required to have a length of pentasaccharide or longer and heparanase Bp acted with a random endolytic action pattern on HP/HS. The specificity and glycohydrolase mechanism of action of heparanase Bp resembles mammalian heparanase and is complementary to the bacterial heparin lyases, which act through an eliminase mechanism on a glucosamine residue (1→4) linked to a UA residue, suggesting its utility as a tool for the structural determination of HP/HS as well as representing a possible model for the medically relevant mammalian heparanase. The utility heparanase Bp was demonstrated by the oligosaccharide mapping of heparin, which afforded resistant intact highly sulfated domains ranging from tetrasaccharide to >28-mer with a molecular weight >9000.